Thermal design analysis of compact heat exchanger using nanofluids. (26th June 2008) - Vasu, V.; Rama Krishna, K.; Kumar, A.C.S.
Compact heat exchangers have been widely used in various applications in thermal fluid systems including automotive thermal fluid systems. Radiators for engine cooling systems, evaporators and condensers for HVAC systems, oil coolers and inter coolers are typical examples that can be found in ground vehicles. Recent development of nanotechnology brings out a new heat transfer coolant called 'nanofluids'. These fluids exhibit larger thermal properties than conventional coolants (water, ethylene glycol, engine oil etc.) due to the presence of suspended nanosized particles in them such as Al2O3, Cu, CuO, TiO2 etc. In this paper, a theoretical analysis was carried with the ε-NTU rating method by using Al2O3 + H2O nanofluid as coolant on flat tube plain fin compact heat exchanger and different characteristics are graphically presented.